Exploration of food preservation potential of Syzygium cumini and Actinidia deliciosa seed extracts - Kiran, S. Sudha; Devi, S. Shalini (International Journal of Scientific Research in Biological Sciences, 2019)
Food spoilage is any change in food which makes it inedible. It is a major challenge in retail and food service, hence proper processing and storage practices are required in food industry. The food manufacturers and processors have achieved high level food preservation through several advanced technologies. Food preservation using natural products of less economic importance has gained prominence in the recent times. In the present research work, Moringa oleifera (Drumstick) leaves, Actinidia deliciosa (kiwi) seed powder, Punica granatum (Pomegranate) seed powder, Allium sativum (Garlic) peel powder, Zingiber officinale (Ginger) peel powder, Syzygium cumini (black plum, jamun) seed powder, Citrus sinensis (Orange) peel powder, Allium cepa (Onion) powder, Trapa natans (water chestnut, singhara) peel powder were tested for its antimicrobial activity against four food spoilage organisms. Of all the products tested, water and ethanolic extracts of S. cumini and A. deliciosa seed powders showed maximum inhibition. The MIC of Syzygium cumini and Actinidia deliciosa seed extracts was determined by Agar well diffusion method. Stability of the extracts at various temperature and pH ranges were also evaluated. S.cumini and A. deliciosa seed extracts were incubated at various temperatures (37o C, 40o C, 50o C, 80o C, 121o C) and pH ranges (2, 4, 8, 10, 12). Syzygium cumini and Actinidia deliciosa were stable at different temperatures, and at different pH ranges only A.deliciosa was stable but not S.cumini. Tomato sauce was incubated with the effective seed extracts and checked for its food preservation efficiency.